Reading Sacred Texts Reliably (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
In arguments about controversies within religious communities the assumption is often made that in basing one’s views on the sacred text there can be no dispute concerning the role of that text with respect to the specific issues of the controversy. Those who participate in the arguments readily make claims about the obviously true meaning of the text. This meaning tends to be the meaning they themselves espouse and which they hold to be the objective meaning of that text. Recent examples of such controversy are the debates about the role of women or the acceptability of homosexuality in the church. In this article I argue that so-called objective readings of the sacred text are in fact subjectivities and that hence objective readings of such texts do not exist. Instead of objective readings I argue for responsible readings and try to show that once we have followed all the rules and procedures that are current for good reading we can do no more than recommend our reading as responsible. But we then do have to accept that there can be more than one responsible reading and that one particular reading cannot automatically trump all others.